Edge Effects on Seedling Diversity Are Mediated by Impacts of Fungi and Insects on Seedling Recruitment but Not Survival - Krishnadas, Meghna; Comita, Liza S. (Frontiers in Forests and Global Change, 2019)
Growing awareness of the role of enemies in plant community dynamics has led to ecologists exploring how plant-enemy interactions change in human-modified systems. Proximity to forest edges was found to weaken the role of two groups of plant enemies—insect herbivores and fungal pathogens—in increasing plant diversity during the seed-to-seedling transition. However, it is less clear whether edge effects similarly compromise the diversifying effects of fungi and insects on established seedlings. We examined this question in a human-modified wet tropical forest in the Western Ghats of southern India. Over an annual cycle of recruitment, in 730 seedling plots (1 x 1-m each) arrayed at distances 0-100 m from the forest edge across 15 locations in a 30 km2 landscape, we suppressed the activity of fungal pathogens and insect herbivores by applying fungicide and insecticide to soil, seeds, and seedlings. Suppressing fungi and insects reduced diversity mainly for seedling recruits and not for seedlings that had already established. However, pesticide effects were only apparent at 90-100 m from forest edges. Specifically, in the interior sites, fungi and insect activity increased recruit diversity, which helped maintain local seedling diversity even though diversity of established seedlings declined with annual mortality. By comparison, canopy openness affected neither the diversity of survivors from the initial seedling cohort nor total seedling diversity after an annual cycle of recruitment. Our results indicate that insects and fungi promote diversity more prominently during early seedling establishment rather than through impacts on post-establishment seedling survival. Thus, edge effects can weaken the diversifying effects of plant-insect and plant-fungal interactions during recruitment and thereby modify the seedling template available for the future tree community in human-modified forests.